Activation of MTOR in pulmonary epithelium promotes LPS-induced acute lung injury. Issue 12 (1st December 2016) - Hu, Yue; Lou, Jian; Mao, Yuan-Yuan; Lai, Tian-Wen; Liu, Li-Yao; Zhu, Chen; Zhang, Chao; Liu, Juan; Li, Yu-Yan; Zhang, Fan; Li, Wen; Ying, Song-Min; et al.
ABSTRACT: MTOR (mechanistic target of rapamycin [serine/threonine kinase]) plays a crucial role in many major cellular processes including metabolism, proliferation and macroautophagy/autophagy induction, and is also implicated in a growing number of proliferative and metabolic diseases. Both MTOR and autophagy have been suggested to be involved in lung disorders, however, little is known about the role of MTOR and autophagy in pulmonary epithelium in the context of acute lung injury (ALI). In the present study, we observed that lipopolysaccharide (LPS) stimulation induced MTOR phosphorylation and decreased the expression of MAP1LC3B/LC3B (microtubule-associated protein 1 light chain 3 β)-II, a hallmark of autophagy, in mouse lung epithelium and in human bronchial epithelial (HBE) cells. The activation of MTOR in HBE cells was mediated by TLR4 (toll-like receptor 4) signaling. Genetic knockdown of MTOR or overexpression of autophagy-related proteins significantly attenuated, whereas inhibition of autophagy further augmented, LPS-induced expression of IL6 (interleukin 6) and IL8, through NFKB signaling in HBE cells. Mice with specific knockdown of Mtor in bronchial or alveolar epithelial cells exhibited significantly attenuated airway inflammation, barrier disruption, and lung edema, and displayed prolonged survival in response to LPS exposure. Taken together, our results demonstrate that activation of MTOR in the epithelium promotes LPS-induced ALI, likely through downregulation of autophagy and the subsequent activation of NFKB. Thus, inhibition of MTOR in pulmonary epithelial cells may represent a novel therapeutic strategy for preventing ALI induced by certain bacteria.